Extracorporeal Shock Wave Therapy Provides Limited Therapeutic Effects on Carpal Tunnel Syndrome: A Systematic Review and Meta-Analysis - Ko-Ta Chen; Yu-Pin Chen; Yi-Jie Kuo; Ming-Hsiu Chiang (Medicina, 2022)
Night wrist splinting has been a conservative treatment for carpal tunnel syndrome. The addition of extracorporeal shock wave therapy provides an alternative treatment. However, strong evidence on the clinical effectiveness of extracorporeal shock wave therapy for carpal tunnel syndrome is still lacking. This study aimed to investigate the effectiveness and safety of extracorporeal shock wave therapy compared with treatments of night wrist splints alone for patients with carpal tunnel syndrome. In this systematic review and meta-analysis, no limitation criteria were used for study selection. All available articles that compare the effectiveness between extracorporeal shock wave therapy combined with night wrist splint and night wrist splint alone for treating carpal tunnel syndrome published up to 20 January 2022 were identified from the databases of PubMed, Embase, and Cochrane Central Register of Controlled Trials Central. The primary outcomes were a standard mean difference with a 95% confidence interval on the improvement of symptom severity and functional impairment between the two groups. In an attempt to analyze trends over time in studies that report repeated measurements, an all time-points meta-analysis (ATM) was undertaken. Seven randomized controlled trials with a total of 376 participants were included in this study. Significant improvements in functional impairment and symptom remission were only observed in the extracorporeal shock wave group at four weeks post-treatment. Extracorporeal shock wave therapy did not demonstrate superior efficacy compared to treatment with night wrist splint alone at 8–10 and 12–14 weeks post-treatment, or through the ATM approach. In conclusion, the therapeutic effect of extracorporeal shock wave therapy is transient and mostly nonsignificant compared with using night wrist splint alone. No serious side effects were reported in all included studies. Other conservative treatments to ameliorate carpal tunnel syndrome symptoms are warranted.